Growth, developmental, and behavioral outcomes of HIV-affected preschool children in Thailand - Oranee Sanmaneechai (2018)
In order to determine growth, developmental, and behavioral outcomes of Thai HIV-affected preschool children, a cross-sectional study was performed at Chiang Mai University Hospital. Thirty HIV-affected children aged 3 to 5 years and 35 of age-matched control with their respective caregivers participated. There was no difference in growth and behavioral outcome, as measured by a standardized Child Behavioral Checklist, between the two groups. Cognitive functioning, as measured by a Thai intellectual assessment score, was significantly lower in the HIV-affected group (p = 0.03). Twenty percent of the HIV-affected group had below average level IQ (≤ 89) compared to 11% in the control. The risk factors were low caregivers' family income and being brought up by relatives as opposed to biological parents. An early intervention program for these children should be promoted as a result.